Tindak Tutur Direktif dalam Buku Kumpulan Cerpen Dua Tengkorak Kepala: Cerpen Pilihan Kompas Tahun 2000 (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study analyzes directive speech acts in the short story collection Dua Tengkorak Kepala: Cerpen Pilihan Kompas Tahun 2000 using the theoretical foundation of pragmatics, where speech acts are understood as doing something by speaking. The main objective of this study is to identify the forms of directive speech acts that appear and describe the functions played by these utterances. The results of the analysis show that in this short story collection, nine types of directive speech acts were found with a total of 38 data. The types of directive speech acts identified, sorted by data frequency, include: ordering (13 data), requesting (9 data), advising (4 data), questioning (3 data), inviting (3 data), begging (2 data), prohibiting (2 data), warning (1 data), and suggesting (1 data). These findings conclude that directive speech acts are very important in forming relationships between characters, advancing the plot, and showing how language is used to influence the actions of interlocutors in literary works.